Primary splenic lymphoma discovered on massive splenomegaly: A case report. (May 2022) - Beji, Hazem; Bouassida, Mahdi; Laamiri, Ghazi; Chelbi, Emna; Nechi, Salwa; Touinsi, Hassen
Abstract: Introduction and importance: Malignant lymphoma occurs in all the systemic organs. Rarely, large B-cell lymphoma is located in the spleen, making the diagnosis difficult. Herein, we report a patient presenting with massive splenomegaly due to LBCL. Splenectomy was essential to assess the diagnosis and to guide postoperative therapeutics. Presentation of a case: A 47-year-old woman, with no comorbidities, complained of weight loss and abdominal pain. She had a palpable spleen that extended below the navel. CT scan revealed massive splenomegaly and lymph nodes in the spleen hilum. Splenectomy was performed. Histopathological examination confirmed the diagnosis of large B-cell lymphoma. The postoperative course was uneventful. Three courses of chemotherapy were given. The patient was in remission after a follow-up of 8 months. Discussion: Massive splenomegaly can be one of the circumstances of the discovery of large B-cell lymphoma. Splenectomy was then essential to confirm the diagnosis and to guide postoperative therapeutics. It also permits reducing hypersplenism and preventing spleen rupture. In patients with high operative risk, splenic needle biopsy should be taken into consideration. Splenic artery embolization before surgery can also be performed in patients having massive splenomegaly to reduce the spleen volume. We highlight the importance of splenectomy to confirm the diagnosis and to relieve the symptoms. Postoperative chemotherapy is essential to prevent relapses. Conclusion: Splenectomy is essential in spleen localized large B-cell lymphoma. It permits to confirm the diagnosis, relieve symptoms, and treatment of underlying hematologic malignancies. Postoperative chemotherapy is essential to prevent relapses. Highlights: Spleen localized large B-cell lymphoma is a rare condition. Massive splenomegaly is rarely a circumstance of discovery of the disease. Splenectomy is essential to confirm the diagnosis and relieve symptoms.